Structures, Policies and Stakeholder Landscape Relevant to Climate Change and Agriculture in the SADC Region - Chevallier, Romy; Gosling, Amanda; Chesterman, Sabrina (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Foresight planning allows governments to construct development narratives of their desired futures and can help policymakers to better frame future policy environments. In this light, foresight can be used to influence SADC’s regional and member state strategies and policy development to ultimately enhance climate-resilient development pathways, including through the use of scenario-guided policy making, strategic planning, regional prioritisation and other foresight approaches. Imagining and anticipating ‘alternative futures’ for the SADC region requires knowledge of its history and context. The purpose of this report it to better understand the system dynamics at play by investigating the regional context, the status quo. As foresight strategies are typically built on existing structures it is important to understand the policy and governance landscape of the SADC region and its member countries.